Pengaruh Implementasi Teknologi Digital dan Kompetensi Sumber Daya Manusia (SDM) Terhadap Efektivitas Sistem Akuntansi Manajemen di Era Industri 4.0 - Ni Nyoman Yuliati; I Made Suardana (Akuntansi research UGR, 2025)
This study aims to examine the influence of digital technology implementation and human resource competence on the effectiveness of management accounting systems in companies located in Mataram City. The research employed a quantitative approach with an associative design. A total of 70 respondents were selected using purposive sampling, and the data were analyzed using multiple linear regression with SPSS version 26. The findings reveal that the implementation of digital technology has a positive and significant effect on the effectiveness of management accounting systems. Similarly, human resource competence also demonstrates a positive and significant impact on system effectiveness. Simultaneously, both variables contribute 40.5% to the improvement of management accounting system effectiveness. These results indicate that the success of management accounting systems in the digital era depends not only on technological adoption but also on the readiness and capability of human resources in managing digital innovation. The practical implications highlight the importance of continuous digitalization strategies and employee competence development to enhance the effectiveness of corporate financial information management.